EFL TEACHERS' BELIEFS IN FOSTERING LEARNER AUTONOMY BY UTILIZING TECHNOLOGY IN ONLINE CLASSROOMS - Yayu Nopriani Martha, - (2022)
Learner Autonomy is a dynamic process in which students take an active role and are responsible for their learning. Moreover, the shifting from traditional or offline to online teaching and learning due to the pandemic of Covid-19 urges the teachers and students to adapt to the situation. Learner autonomy is important in online learning since students and teachers are separated due to distance learning. Students have acquired studying strategies and habits which enable them to define their learning steps. Responding to this situation, research-based information on teachers' beliefs in fostering learner autonomy is necessary to investigate. Fostering learner autonomy is important because This study explores teachers' beliefs in how they foster learner autonomy by utilizing the selected technological tools in online classrooms. Employing a qualitative case study research design, the study collected data from classroom observation, questionnaires, and interviews. The questionnaire involved 115 respondents comprising English teachers from elementary, junior, and senior high schools in some cities in Indonesia. Four English teachers were selected from each level of education based on their teaching experiences and educational degrees. The results from interviews and classroom observations taken from four EFL teachers particularly in two senior high schools, one junior high school, and one elementary school in Indonesia revealed that teachers had been using various technological tools and this practice helped foster learner autonomy in the online classrooms. The teachers revealed that utilizing technology in online classroom gives benefits in fostering learner autonomy. The benefits were learners be focused, purposeful, and more responsible on their learning. Based on the interview and classroom observations, teachers pointed out that utilizing technology in online classrooms makes the students active in managing their own learning. In conclusion, technology is important in fostering learner autonomy in online classrooms. The pedagogical implications drawn from the study are that teachers are expected to develop their understanding and professional development workshop in using technology to foster learner autonomy in online classrooms. This learner autonomy study, however, still requires teachers' support and guidance for the improvement of online teaching and learning in the future.